Multiple primary lung cancers: clinical and genetic features - Nie, Yuntao; Chen, Kezhong; Wang, Jun (Journal of Thoracic Disease, 2018)
It is with great interest that we read the insightful comments by Dr. Fabian and Dr. Yu concerning our recent article in The Journal of Thoracic and Cardiovascular Surgery (1). We feel grateful for their recognition of the value of our article, and would like to respond to the issues that have been raised.